Does Financial Performance Mediate the Impact of Green Accounting and Environmental Performance on Firm Value? - Muhammad Rezi Sudimas; Ramdany Ramdany; Heri Ispriyahadi (Journal of Governance Risk Management Compliance and Sustainability, 2023)
Different environmental issues globally stem from businesses not being accountable for their actions and their effect on nature. Companies taking responsibility by covering their environmental expenses can lower future costs. This paper aims to examine whether financial performance mediates the impact of green accounting and environmental performance on firm value. The approach is quantitative methods using a causality design, applying purposive sampling to test the relationship between variables. The study employs panel data from 2016 to 2021, involving 83 companies, and utilizes path analysis as its analytical method. Based on the findings, it is found that green accounting and environmental performance affect financial performance. While green accounting, environmental and financial performance affect firm value. The relationship between green accounting, environmental performance, and firm value is not mediated by financial performance. It shows that the business is increasing environmental costs and participating in the PROPER award can carry out activities that do not directly harm the environment, and the company is environmentally conscious. This condition fits the legitimacy and stakeholder theory. If the business can focus on environmental management, the community will accept it well, and the company will have a good reputation. High trust and loyalty enhance the company's profits and value. This study varies from other research in that it comprehensively examines the effects of green accounting and environmental performance, both direct and indirect, on financial performance and firm value.